Cell‐free protein synthesis: The transition from batch reactions to minimal cells and microfluidic devices. Issue 4 (30th January 2020) - Ayoubi‐Joshaghani, Mohammad H.; Dianat‐Moghadam, Hassan; Seidi, Khaled; Jahanban‐Esfahalan, Ali; Zare, Peyman; Jahanban‐Esfahlan, Rana
Abstract: Thanks to the synthetic biology, the laborious and restrictive procedure for producing a target protein in living microorganisms by biotechnological approaches can now experience a robust, pliant yet efficient alternative. The new system combined with lab‐on‐chip microfluidic devices and nanotechnology offers a tremendous potential envisioning novel cell‐free formats such as DNA brushes, hydrogels, vesicular particles, droplets, as well as solid surfaces. Acting as robust microreactors/microcompartments/minimal cells, the new platforms can be tuned to perform various tasks in a parallel and integrated manner encompassing gene expression, protein synthesis, purification, detection, and finally enabling cell‐cell signaling to bring a collective cell behavior, such as directing differentiation process, characteristics of higher order entities, and beyond. In this review, we issue an update on recent cell‐free protein synthesis (CFPS) formats. Furthermore, the latest advances and applications of CFPS for synthetic biology and biotechnology are highlighted. In the end, contemporary challenges and future opportunities of CFPS systems are discussed. Abstract : Cell‐free (protein) synthesis combined with lab‐on‐chip microfluidic devices and nanotechnology offers minimal cells/microcompartments that can be tuned to perform various tasks in a parallel and integrated manner from simple gene synthesis to mimicking complex tissue‐like behaviors.